Production of natural flavor compounds using Bacillus subtilis-fermented soybean meal extract and their biological potential: a comprehensive in vitro study - Abd-Alrahman, Abeer M.; Ramadan, Manal M.; Maraay, Mohamed F.; Salem, Rabab; Saleh, Fatma M.; Hashim, Mahmood A; Zhernyakova, Anastasia; El-Messery, Tamer M. (Frontiers in Nutrition, 2024)
This study aims to investigate the production of natural flavor compounds through the utilization of Bacillus subtilis-fermented soybean meal extract and evaluate their biological potential. The experiment involved a comprehensive in-vitro investigation to assess the capabilities and effects of the produced flavor compounds. The flavor production ability of Bacillus subtilis through solidstate fermentation of soybean meal was evaluated. The resulting flavor was subjected to various in-vitro tests to assess its properties, including cytotoxicity, antioxidant activity, anticancer potential, antiviral activity, and antimicrobial activity. Bacillus subtilis strain NRCZ144 was used.To enhance the fermentation process, soybean meal extract was fortified with a combination of L-Lysine and L-Threonine. Gas chromatography-mass spectrometry (GC/MS) analysis was conducted on the fermented soybean meal using two strains of Bacillus subtilis, namely NRCH123 and NRCZ144. This analysis revealed the presence of various volatile compounds in all extracts, including Butylated hydroxytoluene. The extract (SLT2), Bacillus subtilis NRCZ144 (B2)fermented soybean meal and fortified with a combination of 2.5% (w/w) L-Lysine and 2.5% (w/w) L-Threonine, exhibited a rich profile of flavor compounds, with Eucalyptol being identified as the predominant compound. The antioxidant activity of the SLT4 extract was found to be 72.04% at a concentration of 100 μg/mL, indicating significant antioxidant potential. Furthermore, when tested against the human liver cancer cell line HepG2, the extract demonstrated anticancer activity with an IC50 value of 2.26 μg/mL. The extract exhibited potent cytotoxicity, with an IC50 value of 1.02 μg/mL. Importantly, the SLT2 extract displayed strong antibacterial and antifungal activity, even at very low concentrations. The extract's antimicrobial properties indicate its potential for inhibiting the growth of bacteria and fungi.